Spectral Asymmetry of Near-Concentric Traveling Ionospheric Disturbances Due to Doppler-Shifted Atmospheric Gravity Waves - Azeem, Irfan (Frontiers in Astronomy and Space Sciences, 2021)
Atmospheric Gravity Waves (AGWs) excited by meteorological sources are one of the prominent sources of variability in the ionosphere. Partially-concentric Traveling Ionospheric Disturbances (TIDs) associated with AGWs launched by convective storms have been reported in Total Electron Content (TEC) data from distributed networks of Global Navigation Satellite System (GNSS) receivers. In this paper, TEC data from GNSS receivers in the COntiguous United States (CONUS) are presented to examine AGWs in the ionosphere generated by a convective thunderstorm on April 28, 2014 over Mississippi (MS) and Tennessee (TN). Our analysis of the TID perturbations in the TEC data shows zonal asymmetry of the wave frequencies. This spectral asymmetry is examined to determine the effects of the background neutral wind on the intrinsic periods of the underlying AGWs. This work shows that if the relative motion of the TID wavefronts and the background neutral wind is in the opposite direction, the intrinsic periods will decrease and if they both travel in the same direction, the intrinsic periods will increase. Furthermore, our results show that the characteristics of the TIDs observed on April 28, 2014 in the TEC over CONUS are consistent with those of underlying AGWs being excited by a point source, such as a deep convection system.